Reverse transcription Loop-mediated isothermal amplification을 이용한 Soybean mosaic virus의 진단 - 배순도(Soon Do Bae); 김현주(Hyun Joo Kim); Bishwo P. Mainali; 박인희(In Hee Park); 이수헌(Su Heon Lee); 강항원(Hang Won Kang); 김봉섭(Bong Sub Kim); 윤영남(Young Nam Yoon); 이영훈(Yeong Hoon Lee); 배대현(Dae Hyeon Bae) (Sigmulbyeong yeon'gu, 2015)
Soybean mosaic virus (SMV) is a prevalent pathogen that causes significant yield reduction in soybean production worldwide. SMV belongs to potyvirus and causes typical symptoms such as mild mosaic, mosaic and necrosis. SMV is seed-borne and also transmitted by aphid. Eleven SMV strains, G1 to G7, G5H, G6H, G7H, and G7a were reported in soybean varieties in Korea. A reverse transcription loop-mediated isothermal amplification (RT-LAMP) method allowed one-step detection of gene amplification by simple procedure and needed only a simple incubator for isothermal template. This RT-LAMP method allowed direct detection of RNA from virus-infected plants without thermal cycling and gel electrophoresis. In this study, we designed RT-LAMP primers named SML-F3/B3/FIP/BIP from coat protein gene sequence of SMV. After the reaction of RT-LAMP, products were identified by electrophoresis and with the detective fluorescent dye, SYBR Green I under daylight and UV light. Optimal reaction condition was at $58^{°}C$ for 60 min and the primers of RT-LAMP showed the specificity for nine SMV strains tested in this study. Soybean mosaic virus(SMV)는 potyvirus 속에 속하며, 모자이크, 괴사, 기형 등의 병징을 야기하고 국내에서는 11개 계통(G1 to G7, G5H, G6H, G7H, G7a)이 보고되어있다. Reverse transcription loop-mediated isothermal amplification(RT-LAMP) 방법은 등온에서 유전자 증폭이 가능하게 하며, 이 방법은 PCR 과정이나 전기영동 없이도 바이러스에 감염된 식물을 검출할 수 있는 이점이 있다. RT-LAMP의 최적반응 조건은 $58^{°}C$, 60분으로 확인되었다. 특이성 검정을 위해 콩에서 발생하는 여러 바이러스들과 보유중인 SMV의 9 계통에서 그 특이성을 확인하였다. 그 결과 SMV에 대한 RT-LAMP primer들의 종 특이성이 확인되었으며, SMV의 계통들에 대해서도 적용이 가능한 것으로 확인되었다. 항온수조와 heating block과 같은 간편한 등온 장치에서 재현성을 확인하기 위해 Thermocycler 기기와 비교하여 증폭 여부를 확인한 결과 반응의 차이는 나타나지 않았다. RTLAMP 반응 이후, 반응물을 전기영동과 SYBR Green I을 이용하여 자연광과 UV광에서 증폭 여부를 확인하였다. 그 결과 전기 영동, 자연광, portable UV light와 UV transilluminator에서 모두 반응이 확인되었다.